G231(P) Hairstyling hazards and other non-scald burns in children-results from a prospective UK study. (27th April 2016) - Johnson, E; Maguire, S; Kemp, AM; Nuttal, D; Rea, D; Hollen, L; Emond, A
Abstract : Aims: To identify the causes and mechanisms of unintentional non-scald burns among children presenting to hospital, and their associated clinical and social characteristics. Methods: A prospective cross-sectional study was conducted across two UK centres (four Emergency Departments (ED), two Minor Injury Units and one burns unit) between 15/01/2013–31/12/2014. Standardised data collection was performed for all children aged 0–16 completed years with a burn (contact, flame, caustic, electric, radiation, friction). Data recorded included: demographics, burn agent, mechanism and environment, location of the burn on the body, severity, total body surface area (TBSA) and first aid applied. House fires, fatalities and burns due to maltreatment were excluded. Results: Data was ascertained on 85% of children presenting with burns. Of 424 children identified, 34 were excluded due to safeguarding concerns, and one had multiple missing data. The 389 cases (59% boys) included: 86.6% (337/389) contact burns, 3.6% (14/389) sunburns, 3.3% (13/389) caustic burns, 3.1% (12/389) flame burns, with remaining 3.3% (13/389) other causes. The mean age of children sustaining non-scalds burn was 4 years (SD 4.3), the median age was 2 years (CI 2–3). Peak prevalence was at one year (27%, 105/390), while 74.3% (289/389) were aged 5 years or younger. The most common agents causing contact burns are hairstyling devices (67/337, 19.9%) including hair straighteners (15.4%, 52/337), curling tongs (4.2%, 14/337) and hair dryers (0.3%, 1/337). While 85.1% (57/67) of burns from hairstyling devices were to children aged ≤ 5 years old, in contrast, 75% (9/12) of flame burns and 46.1% (6/13) of caustic burns occurred in children >5 years old. TBSA was <2% in 92% (292/317) cases overall, two cases had TBSA >5%, both being flame burns (0.6%, 2/317) (72 cases had TBSA missing). First aid was given to 90.5% (352/389) of children, but only 23.6% (61/258) used cool running water for ≥20 min as recommended by national guidelines. Conclusions: Hairstyling devices pose a major threat to children aged less than five years, warranting a targeted prevention campaign. While first aid was frequently attempted, appropriate first aid was uncommon.